2007
DOI: 10.1248/cpb.55.1512
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolism. Part 8. The Pyranocoumarin, Decursin

Abstract: Microbial transformation of the cancer chemopreventive agent, decursin (1) with Sepedonium chrysospermem (ATCC 13378) yielded two metabolites, (؉)-decursinol (2) and (؊)-cis-decursidinol (3). The structures were established by spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The m / z ratio of the metabolite was determined to be 247 [M + H] + (calcd for C 14 H 15 O 4 , 247). Both 1 H NMR spectra and molecular mass data were in accordance with published data for decursinol . Thus, the isolated metabolite was successfully identified as decursinol.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The m / z ratio of the metabolite was determined to be 247 [M + H] + (calcd for C 14 H 15 O 4 , 247). Both 1 H NMR spectra and molecular mass data were in accordance with published data for decursinol . Thus, the isolated metabolite was successfully identified as decursinol.…”
Section: Resultssupporting
confidence: 84%
“…Decursinol has been prepared by organic synthesis , , which started from the commercially available compounds umbelliferone and esculetin and resulted in the desired product but required 8 and 10 reaction steps, respectively . Synthesis of decursinol has been recently achieved more efficiently by using a microbial system . Herath et al reported the production of decursin metabolites by microbial transformation.…”
Section: Resultsmentioning
confidence: 99%
“…However, little is known about the systemic exposure of decursin after administration because the pharmacokinetics of decursin has not been characterized well in vivo as compared to its in vitro pharmacological activity. The only exception is the observation that decursin may be metabolized to decursinol which is also pharmacologically active [5,18,19]. Decursinol has as well various pharmacological activities, including analgesic, serotonergic, antiangiogenic, and anticancer effects [20][21][22][23].…”
mentioning
confidence: 99%
“…Spinosin, a C-glycoside flavonoid of semen Zizhiphi Spinozae, potentiated pentobarbital-induced sleep in mice via a serotonergic mechanism (Wang et al, 2008). Microbial transformation with Sepedonium chrysospermem of decursin yielded two metabolites, decursinol and cis-decursidinol (Herath et al, 2007). It was shown that decursinol may act as a chemopreventive agent to suppress the uncontrolled growth and invasive potential, angiogenic and metastatic targets, of prostate cancer (Singh & Agarwal, 2006).…”
Section: Discussionmentioning
confidence: 99%